Autophagy related genes polymorphisms in Parkinson’s Disease; A systematic review of literature - Parastoo Yousefi; Shahrzad Ghadirian; Maryam Mobedi; Mehrzad Jafarzadeh; Adib Alirezaei; Ali Gholami; Alireza Tabibzadeh (Clinical Parkinsonism & Related Disorders)
Background: Neurodegenerative diseases are mainly a consequence of degenerated proteins in neurons. Parkinson’s disease (PD) is one of the most common neurodegenerative disorders and is characterized by Lewy body deposition. Autophagy is known as one of the cell maintenance mechanisms. Autophagy targets are damaged or degenerated macromolecules and organelles for lysosomal degradation. The role of disrupted autophagy in PD was established earlier. In this regard, the current study aimed to evaluate the frequency and status of the autophagy gene polymorphisms in PD by a systematic review approach. Materials and methods: In the current study, electronic databases including Scopus, PubMed, and Science Direct were used for the search. The search was performed by using Parkinson’s disease, autophagy, autophagy-related gene, ATG, Single-nucleotide polymorphisms, variant, Sequence variants, and with a date limitation of 2010 to 2023. All original research papers in the English language that evaluate the ATG polymorphisms in PD were included in the study. Results: The conducted search leads to 2626 primary studies screened based on the inclusion criteria. After the screening stage, 8 studies were included. ATG7 rs1375206 and ATG5 rs510432, rs573775 and rs17587319 were associated with PD. However, some other polymorphisms in ATGs that were not associated with PD were listed. Conclusion: In conclusion, regardless of the critical role of autophagy in PD pathogenesis, it seems that ATG16 and ATG7 polymorphisms are not associated with PD; however, ATG7 rs1375206 needs more evaluation for a clearer conclusion in future studies. ATG5 and ATG12 polymorphisms seem to be more important in PD. More comprehensive studies about all ATG5, 7, 12, and 16 seem to be urgently required for a conclusive judgment about their role in PD or even other neurodegenerative disorders.